Overuse of Troponin? A Comprehensive Evaluation of Testing in a Large Hospital System. Issue 5 (1st May 2017) - Wilson, Gibbs; Barkley, Kyler; Slicker, Kipp; Kowal, Robert; Pope, Brandon; Michel, Jeffrey
Abstract : Troponin assays are integral to the diagnosis of acute myocardial infarction (AMI), but there is concern that testing is over utilized and may not conform to published guidelines. We reviewed all testing performed at 14 hospitals over 12 months and associated troponin values with the primary and secondary diagnoses for each visit. Troponin was determined to be negative, indeterminate or elevated based on reference ranges. The majority of troponin measurements were single, not serial (64%). The rate of AMI was low, with only 3.5% of tested patients having a primary or secondary diagnosis of AMI. Sensitivity, specificity and negative predictive value were excellent, exceeding 90%. However, positive predictive value was low, suggesting testing of populations with diseases known to be associated with elevated troponin levels in the absence of AMI. The majority (79%) of elevated troponin values were associated with primary diagnoses other than AMI. Only 28% of elevated troponins were associated with a primary or secondary diagnosis of AMI. These data suggest possible overuse of troponin testing in our healthcare system.